就是这样做的,可以看看!
C(0,n)+2C(1,n)+3C(2,n)+...+(r+1)C(r,n)+...+(n+1)C(n,n)=___(n
3个回答
相关问题
-
组合求证!C(n,r-1)+C(n+1,r-1)+C(n+2,r-1)+...+C(n+k,r-1)=C(n+k+1,r
-
C(n,0)+C(n,1)+C(n,2)+…+C(n,n-2)+C(n,n-1)+C(n,n)为什么等于什么
-
C(0,0)+1/2C(1,n)+1/3C(2,n)+…1/kC(k-1,n)…+1/(n+1)C(n,n)=1/(n+
-
求证:C0n+2C1n+3C2n+…+(n+1)Cnn=2n+n•2n-1.
-
求C(n,0)+C(n,1)+C(n,2)+……C(n,n-1)+C(n,n)的值
-
求证:C0n+3C1n+5C2n+…+(2n+1)Cnn=(n+1)2n.
-
C(n,1)+3C(n,2)+...+3^(n-1)C(n,n)=?
-
组合:C(n,0)+C(n,1)+……+C(n,n)=n^2
-
计算方程P=C/(1+r)+C/(1+r)^2+······+C/(1+r)^n+F/(1+r)^n其中P C N 全是